Učinki usposabljanj za sistem za zgodnje obveščanje in hitro odzivanje (ZOHO) na tujerodne vrste v slovenskih gozdovih - Rantaša, Boris (Gozdarski vestnik, 2021)
Identifying alien invasive species (IAS) in the field and fast response to new IAS findings in forests represent one of the key challenges of modern forestry. Aiming to intensify the capacities for early detection of non-native species in forests, 33 training courses in Slovenia and one abroad were performed in the framework of the project Awareness, Training, and Actions for Non-Native Species in Forests (LIFE ARTEMIS) project taking place in years 2016-2020. A total of 1,059 participants attended the training courses. The training courses were performed for the training performers, professionals, forest owners, volunteers, and employees in the companies, connected with the forest. The training goals of these training courses were achieved. The analysis of the self-evaluation questionnaires showed that the participants had been little to fairly trained before the training and fairly to well-trained afterwards. Before the training, less than half of the respondents had known how to respond when noticing IAS in the forest. After the training, over 90 % of the respondents knew it. After the training for transferring the early warning and rapid response (EWRR) system into other European countries, over 80 % of the respondents answered that they learned something new about IAS. 79 % of the respondents wish to take part in the EWRR system also in the future. The participants want, above all, additional knowledge in the field of IAS detection and more field training in the future. In our article, we present the results of the training success monitoring and the discussion about an eventual need for additional training in the field of informing and fast response for non-native species in the forest space.
Keywords: gozdovi; invazivne tujerodne vrste; izobraževanje; sistem za obveščanje; Slovenija